Genome-wide reverse genetics framework to identify novel functions of the vertebrate secretome. - Michael A Pickart; Eric W Klee; Aubrey L Nielsen; Sridhar Sivasubbu; Eric M Mendenhall; Brent R Bill; Eleanor Chen; Craig E Eckfeldt; Michelle Knowlton; Mara E Robu; Jon D Larson; Yun Deng; et al. (PLoS ONE, 2006)
Understanding the functional role(s) of the more than 20,000 proteins of the vertebrate genome is a major next step in the post-genome era. The approximately 4,000 co-translationally translocated (CTT) proteins - representing the vertebrate secretome - are important for such vertebrate-critical processes as organogenesis. However, the role(s) for most of these genes is currently unknown.We identified 585 putative full-length zebrafish CTT proteins using cross-species genomic and EST-based comparative sequence analyses. We further investigated 150 of these genes (Figure 1) for unique function using morpholino-based analysis in zebrafish embryos. 12% of the CTT protein-deficient embryos resulted in specific developmental defects, a notably higher rate of gene function annotation than the 2%-3% estimate from random gene mutagenesis studies.This initial collection includes novel genes required for the development of vascular, hematopoietic, pigmentation, and craniofacial tissues, as well as lipid metabolism, and organogenesis. This study provides a framework utilizing zebrafish for the systematic assignment of biological function in a vertebrate genome.